Potensi Ekstrak Kulit Buah Manggis (Garcinia mangostana L.) Buatan Pabrik Terhadap Peningkatan Aktivitas Mikrobisidal Sel Neutrofil yang Dipapar Streptococcus mutans (The Potency of Manufactured Mangosteen Peel Extract (Garcinia mangostana L.) Towards In - Hamidah Azzahra; Peni Pujiastuti; Purwanto Purwanto (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
Abstrac Neutrophils are the first non-specific immune cells that successfully overcome the presence of antigens, starting with attachment and then terminate the antigen by phagocyte process. Mangosteen peel extract (Garcinia mangostana L.) possesses a compound that contains pharmacological activity. The purposes of this study were to determine the benefits of manufactured mangosteen peel extract toward increased neutrophil microbicidal activity and the most effective concentration in increasing neutrophil microbicidal activity exposed to S. mutans. Microbicidal activity of neutrophil cells was tested by firstly taking blood isolate neutrophils from peripheral veins of healthy people, secondly incubated with mangosteen peel extract, thirdly exposed to S. mutans, fourthly subcultured on a BHI-A medium, then incubated for 24 hours, and finally calculated the number of colonies by using colony counter. Results of the data were analyzed by using Kolmogorov-Smirnov, Levene, Kruskal-Wallis and Mann-Whitney. The results showed each treatment group had significant difference with value of 0,001 (p<0,05). The treatment group incubated with the mangosteen peel extract had less number of colonies compared to the group which was not given mangosteen peel extract. In conclusion, the mangosteen peel extract could increase neutrophils microbicidal activity that was exposed to S. mutans.. Keywords: mangosteen (Garcinia mangostana L.), microbicidal, neutrophil